SMKN 2 SURABAYA SEBAGAI PENYEDIA JASA PERHITUNGAN RENCANA ANGGARAN BIAYA (RAB) - Retno Sri Herdianti; Supriyanto, Yunaidi (Jurnal Qua Teknika, 2024)
The entrepreneurial product that will be discussed in this article is BoQ (Bill of Quantity). BoQ is a calculation or cost estimate used to build a project. The RAB contains wage prices, material prices, equipment rental prices, and other budgets for the construction of the project. BoQ is a plan for estimating the construction costs of a project. BoQ is created before the project is carried out. The purpose of making a BoQ is to (1) calculate the overall costs starting from wages, materials, equipment and other additions in detail, (2) The owner knows the costs that will be incurred so that he can estimate the funds he has to build a project carefully and efficiently, (3) obtain data on the amount of material that will be used in the construction of the project. SMK Negeri 2 Surabaya produces graduates who are competent and ready to work as estimators. This is supported by SMK Negeri 2 Surabaya which has a complete engineering laboratory as well as qualified human resources for teachers and educational staff. The methods used in implementing the BoQ calculation service entrepreneurship program include preparation, market research and product formulation, and marketing strategies.